19a-10a-a-3a=10

Simple and best practice solution for 19a-10a-a-3a=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19a-10a-a-3a=10 equation:


Simplifying
19a + -10a + -1a + -3a = 10

Combine like terms: 19a + -10a = 9a
9a + -1a + -3a = 10

Combine like terms: 9a + -1a = 8a
8a + -3a = 10

Combine like terms: 8a + -3a = 5a
5a = 10

Solving
5a = 10

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '5'.
a = 2

Simplifying
a = 2

See similar equations:

| (4x^2-3x-40)=0 | | x-2=7x-2 | | x^2-8x+16=12-16 | | 6.7+w=-1.10 | | -2(6T-6T-6T)=-120 | | 8(3x-2)+6=7(-6x-20)-2 | | 3p-2-7p=-5+p-4-4p | | 28(-5+y)+11y=16 | | -16y-1+16y=-12 | | 8(3x-2)+6=7(-6x-20)-1 | | x(1+4)=x | | 8y+7=23 | | 8(3x-2)+6=7(-5x-20)-1 | | x^2+12x=-43 | | 3p-2-7p=-5+p-4p | | 3x^2*8x^5= | | n-3=-4n-(n-3) | | 2y-3y+-1=4 | | -7(3r-4)=-20+9r | | 28-13.8x=-54.8 | | 4s-12*(s-2)=s | | 20z+3z-21z-1=13 | | -78=6U+12 | | 3x-3+x-3=90 | | (6x^3y^2)(-2x^2y)= | | -6+3(1-8k)=27 | | -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x |

Equations solver categories